HACS: Helical Auxetic Yarn Capacitive Strain Sensors with Sensitivity Beyond the Theoretical Limit (Adv. Mater. 10/2023). Issue 10 (10th March 2023) - Cuthbert, Tyler J.; Hannigan, Brett C.; Roberjot, Pierre; Shokurov, Alexander V.; Menon, Carlo
Abstract : Capacitive Strain Sensors In article number 2209321, Tyler J. Cuthbert, Carlo Menon, and co‐workers present a novel capacitive strain sensor that accesses sensitivity beyond the theoretical limit. The helical auxetic capacitive sensor (HACS) employs a two‐component yarn structure allowing tuneable sensitivity and accessible strain ranges. The HACS sensitivity is found to be from an engulfment phenomenon, which is predicted with a geometric model and analyzed by X‐ray μCT scanning.